China's economy a collection of surveys - Claus, Iris; Oxley, Les (Wiley-Blackwell, 2015)
"This collection of critical surveys provides readers with a range of up-to-date work from leading scholars in the area, writing on some of the key issues facing China, as they survey the present and future challenges of the Chinese economy Nine papers provide detailed discussion on key aspects of the past, present and future of the Chinese economy Leaders in their relevant fields of scholarship tackle some of the critical issues facing China Contributors identify common themes, including the household registration system, urbanization, demographic transition, inequality and the sustainability of economic growth Articles provide a critical review of the literature and discuss policy implications and areas for future research "-- Provided by publisher.